A cost-efficient smart solution for small scale farmers: a multidisciplinary approach - Brenes Carranza, José Antonio (2020)
In the near years, the world population will have to deal with a big problem: to reduce the food required to satisfy its increasing demand. It is imperative to support farmers to find a solution . In this regard, the information and communication technologies (ICT) sector can help by creating technology which supports agriculture processes to increase the crop production and to reduce the resources consumption. In this paper, we present a cost-efficient solution for small-scale farmers. Our platform helps the farmers in the decision making process by using data recollected from crops and by controlling fertigation. Using it, farmers can be more efficient and waste fewer resources.